(3ejRGf GdeYOdI aj TCf GdHSedIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3eMehO UObi s)
(3ChdgG (B:s
(3GdMeO ddg hGdUdGI hGdSdGe Ydi QShd Gddg Udi dGdg Ydjg hSde bO ETJgQ cdGe GdfGS ai TCf GdHSedI hGMJLGLge Ydi CfgG bQBf Ch ZjQ bQBf hTfY GdbGVi CHhHcQ GdHGbdGfi hZjQg Ydi GdTGaYi ai EKHGJgG bQBfkG s
(3BNQgG (B:s
(3bGd UdjJ Nda CHj gQjQI abQCf HSe Gddg GdQMef GdQMje be bQCf HCe GdbQBf aPcQ GdMOjK hai BNQg adeG Sde bGd hGdPi faSi HjOg Efi dCTHgce UdGI HQShd Gddg Udi Gddg Ydjg hSde gPG MOjK UMjM dGYdg dg hgh CUM eG hQO ai GdHGH Hd de jUM ajg MOjK ZjQg EfJs
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1918s
Keywords: (3Gdabg GdESdGejs